yearling newbery: the cricket in time square - Selden, George; George Selden (New York Bantam Doubleday Dell books for young readers, 1960)
The Cricket in Times Square (a 1961 Newbery Honor Book) follows Chester, a musical country cricket accidentally transported from Connecticut to a New York City subway station. Befriended by Mario Bellini, Tucker Mouse, and Harry Cat, Chester becomes a famous musician but ultimately misses his home and returns to the countryside.
English